Survival of HIV-infected children: A cohort study from the Asia-Pacific region - Lumbiganon P. (2017)
Background: Combination antiretroviral therapy (ART) has been used for HIV-infected children in many Asian countries since 2002. This study describes survival outcomes among HIV-infected children in a multicenter regional cohort in Asia. Patients and Methods: Retrospective and prospective data collected through March 2009 from children in 5 countries enrolled in TREAT Asia's Pediatric HIV Observational Database were analysed. Multivariate Cox proportional hazard models were used to assess factors associated with mortality in children who received ART. Results: Among 2280 children, 1752 (77%) had received ART. During a median follow-up of 3.1 years after ART, 115 (6.6%) deaths occurred, giving a crude mortality rate of 1.9 per 100 child-years [95% confidence interval (CI): 1.6 to 2.4]. The mortality rate was highest in the first 3 months of ART (10.2 per 100 child-years; 95% CI: 7.5 to 13.7) and declined after 12 months (0.9 per 100 child-years; 95% CI: 0.7 to 1.3). Those with a low recent CD4 percentage, who started ART with lower baseline weight-for-age Z score, or with WHO clinical stage 4 had an increased risk of death. Of 528 (23%) children who never received ART, 36 (6.8%) died after presenting to care, giving a crude mortality rate of 4.1 per 100 child-years (95% CI: 3.0 to 5.7), with a lost-to-program rate of 31.5 per 100 child-years (95% CI: 28.0 to 35.5). Conclusions: The high mortality during the first 3 months of ART and in those with low CD4 percentage support the implementation of early diagnosis and ART initiation. © 2011 Lippincott Williams & Wilkins.